2016
DOI: 10.1002/2016gl068519
|View full text |Cite
|
Sign up to set email alerts
|

Earlier onset of the spring fine dust season in the southwestern United States

Abstract: Particulate matter (PM)2.5 dust concentrations (mineral particles with aerodynamic diameters less than 2.5 µm) typically peak in spring and early summer at rural and remote sites across the southwestern United States. Trend analyses indicate that springtime regional mean PM2.5 dust concentrations have increased from 1995 to 2014, especially in March (5.4% yr−1, p < 0.01). This increase reflects an earlier onset of the spring dust season across the Southwest by 1 to 2 weeks over the 20 year time period. March d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
90
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 76 publications
(100 citation statements)
references
References 75 publications
(103 reference statements)
8
90
0
Order By: Relevance
“…The weak dust increase in summer is related to higher soil moisture and vegetation cover, increased monsoon (rainy season) precipitation, and lower incidence of synoptic‐scale dust‐inducing weather phenomena (fronts and cyclones) in the southwestern United States. In addition, the dust season, defined by the length between the first and last events detected at these sites, has become longer (see section S2 for details), consistent with an earlier onset of dust events reported by Hand et al [2016]. Climate models have robustly predicted an incipient spring drying trend in this region [ Seager et al ., 2007; Cook et al ., 2015; Dai , 2013; Gao et al ., 2014], and the observed dust trend could thus be an early signal of its development.…”
Section: Intensification Of Dust Storm Activitysupporting
confidence: 83%
See 1 more Smart Citation
“…The weak dust increase in summer is related to higher soil moisture and vegetation cover, increased monsoon (rainy season) precipitation, and lower incidence of synoptic‐scale dust‐inducing weather phenomena (fronts and cyclones) in the southwestern United States. In addition, the dust season, defined by the length between the first and last events detected at these sites, has become longer (see section S2 for details), consistent with an earlier onset of dust events reported by Hand et al [2016]. Climate models have robustly predicted an incipient spring drying trend in this region [ Seager et al ., 2007; Cook et al ., 2015; Dai , 2013; Gao et al ., 2014], and the observed dust trend could thus be an early signal of its development.…”
Section: Intensification Of Dust Storm Activitysupporting
confidence: 83%
“…This finding confirms earlier observations of the dust trends using rainfall and snow deposition, surface fine soil, and aerosol optical depth data [ Brahney et al ., 2013; Clow et al ., 2016; Sorooshian et al ., 2011; Hand et al ., 2016]. The climate analysis further links the dust trend with large‐scale climate variations, particularly the SST oscillation in the Northern Pacific, as described by PDO variability.…”
Section: Discussionmentioning
confidence: 99%
“…5). More details regarding IMPROVE stations, sampling, and the analysis method can be found in previous studies (Hand et al, 2011(Hand et al, , 2012(Hand et al, , 2016.…”
Section: Improve Fine Dustmentioning
confidence: 99%
“…Due to its long temporal coverage, this dataset has been widely used to study long-term variations in surface fine dust in the US. Using IMPROVE data, Hand et al (2016) found an increasing trend of fine dust in spring in the southwestern US during 1995-2014 and related this trend to a negative Pacific decadal oscillation (PDO) from 2007 to 2014. Tong et al (2017) also found a rapid increase in dust storm activity in the southwestern US from 1988 to 2011 and related the trend to sea surface temperature variations in the Pacific.…”
Section: Introductionmentioning
confidence: 99%
“…The PTFE sample filter is analyzed for absorption by HIPS as described above, as well as for mass by weighing and elemental composition by X-ray fluorescence (XRF). The XRF element most relevant to our analysis is iron (Fe), which is reliably measured (Hyslop et al 2012(Hyslop et al , 2015 and serves as a tracer both for mineral dusts in general (Hand et al 2016) and for absorbing dusts in particular (Fialho et al 2006;Moosmuller et al 2012). The total Fe measured by XRF is not limited to the (hydr)oxides believed responsible for absorption (Lafon et al 2006;Journet et al 2014;Utry et al 2015), but includes structural Fe in nonabsorbing clays.…”
Section: Datamentioning
confidence: 99%